(NpIANIST I EGO RABOTAs (Nu^EBNOE POSOBIE s - (Ns(B.(Ni(B.(NsAW[INSKIJs; (Nl(B.(Na(B.(NbARENBOJMAs (NPOD OB]EJ REDAKCIEJs ((NsANKT(B-(NpETERBURGs (NlANXs (NpLANETA mUZYKIs, 2020)
(NsAMARIJ iLXI^ sAW[INSKIJ (B1891-1968- (NSOWETSKIJ PIANIST I MUZYKALXNYY PEDAGOG(B.s
Keywords: (NmETODIKAs